Eating sustainably: Conviction or convenience?. (1st January 2023) - Waldman, Kurt B.; Giroux, Stacey; Blekking, Jordan P.; Nix, Evan; Fobi, Daniel; Farmer, James; Todd, Peter M.
Abstract: Environmentally sustainable food consumption is one component of addressing climate change. Previous research has largely approached sustainable food consumption by investigating individual behaviors, without a broader conceptualization of what motivates food consumers to act sustainably. Using a representative sample of Indiana consumers, we explore sustainability across a range of food behaviors through latent class analysis, controlling for environmental attitudes, spatial access to food, and consumer demographics. This approach allows us to go beyond consumer segmentation analysis to explore how consumers conceptualize sustainable food behavior. The largest class of consumers (44% of the sample) appear either unwilling or unable to pay more for sustainability but are more likely to engage in sustainable behaviors that intersect with self-oriented attributes such as health benefits and lower cost. A second class (34%) consists of consumers who seem to be primarily motivated by the single issue of buying organic, are on average higher income, more educated, have better access to food, and are not opposed to paying for sustainability. Consumers in the smallest and most highly motivated group (9%) in terms of sustainability attitudes and self-perceived sustainability focus on local food production and are generally rural dwelling with less income. Only 13% of consumers engage in few to no sustainable behaviors, and these people notably exhibit the least sustainable attitudes. These findings illustrate the ways in which food sustainability is more nuanced than often characterized—much of it is driven by convenience and self-interest rather than reputation with respect to sustainability or conviction about environmental outcomes. This work also highlights how a combination of social, psychological, and spatial barriers exists and shape how different consumer groups conceptualize sustainable food consumption.